Risk factor analysis of cognitive frailty in older adults with type 2 diabetes mellitus: a cross-sectional study - Ren, Qingjuan; Niu, Shu; Zhi, Lei; Liu, Hongfang (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive Frailty (CF), characterized by the co-occurrence of physical frailty and cognitive impairment without dementia, is a significant concern in older adults with Type 2 Diabetes Mellitus (T2DM). This study investigates the prevalence and risk factors of CF in this population, addressing the urgent need for early detection and intervention strategies.MethodsA cross-sectional study was conducted among 713 T2DM patients aged ≥65 years. Participants were assessed using the Clinical Dementia Rating (CDR) for cognitive function and Fried Frailty Phenotype (FP) criteria for physical frailty. CF was defined as CDR = 0.5 and FP score ≥ 3. Multivariable logistic regression identified independent risk factors, adjusting for demographic and clinical variables.ResultsThe prevalence of CF was 24.3%. Cerebrovascular disease (OR: 2.39, 95% CI: 1.44–3.97) and peripheral arterial disease (OR: 1.74, 95% CI: 1.03–2.95) were significant risk factors, while higher education (OR 0.85, 95% CI 0.76–0.94) and later diabetes onset (OR: 0.93, 95% CI: 0.88–0.98) were protective. Early-onset diabetes significantly increased CF risk regardless of education level.ConclusionThis study highlights a markedly increased risk of CF in older adults with T2DM, especially in individuals with CVD, PAD, low education levels, or early-onset diabetes. Notably, early diabetes onset may override the protective effects of cognitive reserve, emphasizing the critical need for early metabolic and vascular risk management in this high-risk population. These findings support integrated screening for cognitive and physical frailty in diabetes care to enable timely interventions.